Dynamic development of syntactic complexity in second language writing: A longitudinal case study of a young Chinese EFL learner - Wang, Zhihong (Frontiers in Psychology, 2022)
The present study analyzes the English diaries written by a young Chinese English as a foreign language (EFL) learner over a one-year period in an attempt to determine the developmental process of Chinese EFL young learners’ written language in terms of syntactic complexity. This study aimed to use a wide range of metrics to explore densely collected data based on Dynamic Systems Theory. The longitudinal study data were analyzed through eight large-grained measures related to sentential, clausal, and phrasal features by using L2 Syntactic Complexity Analyzer, as well as fine-grained measures related to seven modifiers, ADJA, CARD, ADJP, ADV, PREP, SUB, and REL, through manual annotations. The results show that, first, the developmental process was not linear but spiral in terms of large-grained measures. The sentential level varied, and the development process of the young learner is different from Chinese English learners studying in colleges. Second, the dynamic features of fine-grained measures are also prominent in the seven indicators. ADJA, PREP, and REL showed a steady increase, ADJP showed an obvious decline, while ADV and SUB first increased and then declined. Third, the correlation analysis revealed a competitive interaction within fine-grained measures and between large-grained and fine-grained measures.